Otpisani (Epizoda 11) - Provala . The Written Off, Episode 11 - Burglary - Đorđević, Aleksandar (RTV Beograd, 1974)
The eleventh episode starts off quietly: Tihi’s group is advised by headquarters to keep a low profile for a while on account of thier recent losses. Unfortunately, Tihi runs into his old school friends Klara, Miro and Joker, the last two of whom support the Germans. Meanwhile, Slavko, a partisan undercover agent working in the police discovers that raids are going to start in Belgrade on the very day when he should meet an important member of the communist headquarters from Zagreb. An artist connected with Tihi’s group is arrested by the special police and Miro and Joker come to look for Tihi who is safe in a hideout. Slavko is ordered to come there, but wants to complete the mission first and as he leaves, Tihi and Prle decide to look after him. The police find a police document which Slavko copied with the artist and a unit is sent after him. Slavko manages to get his Zagreb comrade through the police blockade onto the river dock, but he is seen by the agents as he leaves. Tihi and Prle are still following him; at first they help him to elude the police, but eventually he is caught and murdered.